Genetic Polymorphisms and Cisplatin- Related Nephrotoxicity - Arundhati Bag; Lalit Mohan Jeena; Niladri Bag (Global Journal of Cancer Therapy - Peertechz Publications, 2015)
Cis- diamminedichloroplatinum (cisplatin) is one of the most commonly used present day hemotherapeutic agents. It is used to treat a wide range of cancers including head and neck, lung, gastrointestinal tract, ovarian and genitourinary cancers. However, dose- limiting toxicity is often associated with cisplatin. It is known that cisplatin works more effectively with dose escalation, but significant risk for nephrotoxicity is often associated with higher doses [1]. Recovery of renal function occurs over a period of 2-4 weeks, although lack of recovery can also take place [2]. Kidney accumulates cisplatin in much higher concentration in comparison to other organs and is the major route of its excretion [3]. Five times higher cisplatin concentration was observed in proximal tubular epithelial cells in comparison to serum [4]. Highest accumulation of cisplatin occurs in S3 segment of proximal tubule followed by the distal collecting tubule and the S1 segment of proximal tubule [5]. Cisplatin nephrotoxicity may be presented in various ways of which the most serious presentation is acute kidney injury, which occurs in 20-30% of patients despite hyperhydration and forced Diuresis [6].